Materiales didácticos para estimular las funciones del cerebro en niños de educación inicial del subnivel II de la Unidad Educativa 5 de Junio - Macias Rivera, Ana Paola (2023)
The present work entitled "Didactic materials to stimulate the functions of the brain in children of Initial Education of sublevel II of the educational unit "June 5" is essential, since it is directly based on children from 4 to 5 years of age. of the institution. In this project, the objective is to analyze the importance of didactic materials and their influence on early stimulation in children of sublevel II initial education of the 5 de Junio Educational Unit, of the Isla de Bejucal parish, it is also declared that in In this project, the application of the survey was carried out, in which 100% consider the use of didactic materials essential, because they are part of the resources for teaching and learning that are offered to the infant.